The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/s140610479
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Evaluation of Multipoint Simultaneous CO2 Sampling Wireless Sensors for Livestock Buildings

Abstract: The environment in livestock buildings must be controlled to ensure the health and welfare of both workers and animals, as well as to restrict the emission of pollutants to the atmosphere. Among the pollutants generated inside these premises, carbon dioxide (CO2) is of great interest in terms of animal welfare and ventilation control. The use of inexpensive sensors means that complete systems can be designed with a number of sensors located around the building. This paper describes a study of the suitability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…[31] and Yasuda et al . [32], several different commercially available NDIR CO 2 sensors were compared with a reference method in the laboratory, and concluded that concentrations measured with all sensors agreed well with that of the calibration gas. However, field performance of the selected NDIR technique is still meager in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…[31] and Yasuda et al . [32], several different commercially available NDIR CO 2 sensors were compared with a reference method in the laboratory, and concluded that concentrations measured with all sensors agreed well with that of the calibration gas. However, field performance of the selected NDIR technique is still meager in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64] Occupational health and safety and animal husbandry articles oen report well-ventilated indoor ranching operations with CO 2 concentration in thousands of ppm. [65][66][67][68][69][70] Despite the accepted estimates of GHG emissions from ranching, there is a dearth of literature reporting ground-level outdoor ambient concentrations based on land use. 71,72 Satellite remote sensing efforts to date are only able to measure high altitude columns, resulting in distinctions of <5 ppm from heavy urban to light rural land use.…”
Section: Ch 4 Concentrationmentioning
confidence: 99%
“…This group includes sensors for measuring concentration and pressure of gases, temperature, humidity, and airflow, being observed in 8 publications (14.0% of total publications). These "environmental sensors" were used in broiler houses to measure CO 2 [74] and NH 3 [76] concentrations as part of ventilation control systems [75] to provide information about environmental conditions to farmers [28] and as a component in the gas concentration control when using foam to humanely slaughter broilers in extreme situations [34]. Moreover, environmental sensors were also used in the control of ventilated chamber [30], as part of slaughter chambers used for small-flock depopulation [35], and in a study about the effects of low atmospheric stunning on broilers [64].…”
Section: Environmental Sensorsmentioning
confidence: 99%